1996
DOI: 10.1029/96gl01999
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo modelling of TRM and CRM acquisition and comparison of their properties in an ensemble of interacting SD grains

Abstract: Numerical modelling of TRM and of Haigh's model of CRM acquisition was performed using the Monte‐Carlo method. It was confirmed that for noninteracting particles, i.e. at small volume concentration c < 1% CRM < TRM as was predicted earlier by Stacey and Banerjee and at large grain size, ≈ (0.1–0.2) µm, it may reach values ≈ (4–10)‥ However for strongly interacting systems, i.e. c > (l–3)%, CRM may be ≥ TRM, though CRM can not exceed TRM more than twice. The relative stability to thermodemagnetisation is always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 8 publications
6
19
2
Order By: Relevance
“…Thus, the CRM/TRM relation is a function of T b and T CRM , which means that their blocking temperature spectra are not identical. This conclusion was confirmed later by numerical Monte-Carlo modeling of TRM and CRM acquisition carried out by Shcherbakov et al (1996) who showed, in particular, that for strong magnetostatic interaction-i.e., in the case of a high volume concentration of SD grains-the relation CRM/TRM < 1, valid for non-interacting SD grains, reverses to CRM/TRM > 1. Still, the thermal stability of TCRM and TRM can be compared for a narrow temperature range, so one must be cautious interpreting results obtained on samples having a narrow T b spectrum.…”
Section: Kafan Sectionsupporting
confidence: 58%
“…Thus, the CRM/TRM relation is a function of T b and T CRM , which means that their blocking temperature spectra are not identical. This conclusion was confirmed later by numerical Monte-Carlo modeling of TRM and CRM acquisition carried out by Shcherbakov et al (1996) who showed, in particular, that for strong magnetostatic interaction-i.e., in the case of a high volume concentration of SD grains-the relation CRM/TRM < 1, valid for non-interacting SD grains, reverses to CRM/TRM > 1. Still, the thermal stability of TCRM and TRM can be compared for a narrow temperature range, so one must be cautious interpreting results obtained on samples having a narrow T b spectrum.…”
Section: Kafan Sectionsupporting
confidence: 58%
“…The thermodynamic equilibrium at a given temperature is frozen in by increasing the energy barrier between two competing magnetization states. Current theories of chemical remanent magnetization (CRM) acquisition by grain growth follow this concept [ Kobayashi , 1962; Stacey and Banerjee , 1974; Stokking and Tauxe , 1990; McClelland , 1996; Shcherbakov and Sycheva , 1996], where the blocking condition depends on the isothermal change of the energy barrier with increasing volume.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The ARM is a complicated magnetic acquisition process that is extremely sensitive to the size of the magnetic particles, and to magnetostatic interactions [Egli and Lowrie, 2002;Sugiura, 1979]. These properties are shared with other weak-field magnetizations, such as the thermoremanent and the chemical remanent magnetization [Néel, 1949[Néel, , 1955Shcherbakov et al, 1996]. It is not surprising that modeling of weak-field magnetizations is an extremely difficult task, especially if magnetostatic interactions are included.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are shared with other weak-field magnetizations, such as the thermoremanent and the chemical remanent magnetization [Néel, 1949[Néel, , 1955Shcherbakov et al, 1996]. It is not surprising that modeling of weak-field magnetizations is an extremely difficult task, especially if magnetostatic interactions are included.…”
Section: Introductionmentioning
confidence: 99%